If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4a + -8) = 2(1 + -5a) Reorder the terms: 2(-8 + 4a) = 2(1 + -5a) (-8 * 2 + 4a * 2) = 2(1 + -5a) (-16 + 8a) = 2(1 + -5a) -16 + 8a = (1 * 2 + -5a * 2) -16 + 8a = (2 + -10a) Solving -16 + 8a = 2 + -10a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '10a' to each side of the equation. -16 + 8a + 10a = 2 + -10a + 10a Combine like terms: 8a + 10a = 18a -16 + 18a = 2 + -10a + 10a Combine like terms: -10a + 10a = 0 -16 + 18a = 2 + 0 -16 + 18a = 2 Add '16' to each side of the equation. -16 + 16 + 18a = 2 + 16 Combine like terms: -16 + 16 = 0 0 + 18a = 2 + 16 18a = 2 + 16 Combine like terms: 2 + 16 = 18 18a = 18 Divide each side by '18'. a = 1 Simplifying a = 1
| 0.3x+18.7=x-5.24 | | (D-7)(D+3/4)=0 | | 4a^2-1a+5=15 | | -32+2r=114 | | (4t^2-4/9(t+1)^2)(3t+3/2t-2) | | (x+3)(x-2)=x+3 | | P(x)=-75x^2+15000x | | a=9y+3yx | | -x-24=11x | | 9/2+(-8)=-5.5+4m | | (3y-4y)+(2x+6y)= | | 5x-8x^2=0 | | (9z-12)+3z=180 | | (x-10)(x-4)=0 | | (x-2)(x^2-1)-6x-6=0 | | (4/17)x=16 | | 3x+17x-7=5(4x+3) | | 2L-2(L-12)=156 | | 4t-12=17+9t | | X/1=15/6 | | 10/15 | | 4w+8=5w+1 | | 10x^3y^5/15x^2y | | 8z-13=7+4z | | 3.4=5-w | | 1/2*2x | | 4x-7(x-2)=10 | | 2L+2*(12-L)=156 | | x(x+1)(x-4)+4(x+1)=0 | | 2L+2*(12-L)= | | 4(7x+2)=-300 | | 3b^2-4b-126=0 |